Hubungan Indeks Massa Tubuh Dan Lama Operasi Dengan Kejadian Shivering Pasca Operasi - Yoga Adzi Saputra; Marta Tania Gabriel Ching Cing; Rully Annisa (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Spinal anesthesia is given to patients undergoing surgery on the abdominal area. Spinal anesthesia can interfere with temperature thermoregulation, thereby inhibiting the compensatory response to temperature, causing shivering. The aim of the research was to determine the incidence of shivering in post-operative patients with spinal anesthesia at the Wijayakusuma Hospital , Purwokerto 2023. This research used a quantitative descriptive research design with a cross sectional design. The sample in this study was 40 post-spinal anesthesia patients using non-probability sampling techniques. Data was obtained from direct observation in the IBS room at the Wijayakusuma Hospital, Purwokerto in April-May 2023. The results showed that 19 people (47.5%) experienced shivering and 21 people (52%) did not experience shivering. .5%), the results of the analysis show that there is a relationship between BMI factors and shivering after spinal anesthesia (p value 0.002 <0.05) where shivering occurs most often in respondents with a thin body mass index (<18.5 kg/m) as many as 9 people (22.5%). Then the results of the analysis also showed that there was no difference between the duration of the operation and shivering after spinal anesthesia (p value 0.768 > 0.05).